Investigations into the Phytochemical Composition of Mucuna pruriens (L.) Seeds - Mohammad Salim; I. P. Prajapati; Mayuri Singh (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
This chapter focuses on identifying the phytochemical components and assessing the acute oral toxicity of the methanolic extract obtained from Mucuna pruriens seeds. The process involved collecting mature seeds, drying them at room temperature, crushing them into coarse powder, and using Soxhlet’s extraction technique with methanol. The resulting extract was then concentrated using a rotary flash evaporator, resulting in a semi-solid crude extract with a yield of 09.534%. The phytochemical analysis of the seed extract detected the presence of various compounds, including steroids, alkaloids, tannins, carbohydrates, amino acids, resins, and starch.